Buyer confusion and market prices – a replication study of Kalayci and Potters (2011) - Metsälampi, Satu (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
In this master’s thesis I report my close replication attempt of Kalayci and Potters (2011). They examine experimentally whether some of the complexity in consumer markets could be explained by firms’ attempts to take advantage of consumers bounded rationality. In their experimental markets sellers can try complicate buyers’ evaluation of the qualities of their goods. Their results show that price offers and transaction prices are significantly higher when sellers can use complexity to confuse buyers. This leads Kalayci and Potters (2011) to conclude that buyer confusion can, indeed, constitute a source of market power. The objective of my research is to study whether these results are replicated with a different sample from a similar pool of participants and a different experimenter. To that end, I reproduce the procedures of data gathering and analysis of the original research as exactly as possible. The replication experimental sessions were conducted in Turku University’s PCRC lab in May 2016 using the z-Tree program code employed in the original research, with only minor modifications, including translations into Finnish. The analysis is conducted following the original research and replicability is assessed by set criteria. The results on replicability are mixed: In the replication experimental data, as in the original research, price offers and transaction prices are higher when sellers sell to human buyers, and prices increase with average complexity. These effects are, however, smaller in size, and furthermore, I find that the high and low quality sellers’ prices respond differently to average complexity, which contradicts the original findings. I therefore deem my replication of Kalayci and Potters (2011) a partial success.